2021
DOI: 10.1094/pdis-06-20-1191-re
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Boscalid inBotrytis cinereaFrom Greenhouse-Grown Tomato

Abstract: Grey mold, caused by the fungus Botrytis cinerea Pers ex Fr., is one of the most destructive spoilage diseases, severely affecting tomato production in Henan Province, China. Spraying fungicides from the flowering to the harvest stage is a necessary measure to reduce losses associated with B. cinerea infection. However, B. cinerea has developed resistance to fungicides in many countries. Boscalid is a succinate dehydrogenase inhibitor (SDHI) fungicide, and was registered for the control of grey mold. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…There were irregular point mutations in C subunit of all strains. Zhang's research also found the irregular mutations in the C subunit (Zhang, Han, et al, 2015), and Liu's reports speculate the simultaneous point mutations in the sdhC gene may not be related to the resistance of B. cinerea to boscalid (Liu et al, 2021), which is consistent with our research. At present, the mutation site of SDH is mainly on the SDHB subunit, in addition to the report that the N230I mutation causes the resistance of B. cinerea to fluopyram, the histidine mutation at position H272L/R/Y and the proline mutation at position P225F are relatively common (Gao et al, 2021; Laleve et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There were irregular point mutations in C subunit of all strains. Zhang's research also found the irregular mutations in the C subunit (Zhang, Han, et al, 2015), and Liu's reports speculate the simultaneous point mutations in the sdhC gene may not be related to the resistance of B. cinerea to boscalid (Liu et al, 2021), which is consistent with our research. At present, the mutation site of SDH is mainly on the SDHB subunit, in addition to the report that the N230I mutation causes the resistance of B. cinerea to fluopyram, the histidine mutation at position H272L/R/Y and the proline mutation at position P225F are relatively common (Gao et al, 2021; Laleve et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…In Weber's report, H272Y mutations with high resistance to boscalid showed sensitivity or resistance to fluopyram (Weber et al, 2015); meanwhile, some isolates that are resistant to fluopyram have no mutations in SDHB subunit. Liu's reports showed that no point mutations were found in the SDHB genes of many low‐resistant and moderately resistant strains of B. cinerea (Liu et al, 2021). Moreover, in the SDHB of some of these isolates, mutations were detected, and some of them were not detected (Amiri et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…cinerea has developed resistance to different kinds of fungicides. B. cinerea resistance to SDHI fungicides has been reported in multiple areas [15,16,26,27]. In the current study, the resistance isolates of B. cinerea to penthiopyrad were sampled from tomatoes from commercial greenhouses in Hebei Province and tested by the mycelial growth assay.…”
Section: Discussionmentioning
confidence: 99%
“…The Fusarium graminearum with the point mutants SdhB H248Y/R exhibit decreased sensitivity to pydiflumetofen [14]. In the sensitive and low-resistance isolates of B. cinerea to boscalid, four simultaneous dependent mutations in the sdhC subunit (G85A, I93V, M158V, and V168I) were detected [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation